Hubungan Ketahanan Pangan dengan Asupan Protein di Kecamatan Selo Boyolali - Bagus Rizky Nur Hidayat; Luluk Ria Rakhma; Listyani Hidayati (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Based on the Global Food Security Index (GFSI), Indonesia has a score of 60.2 and ranks 63rd out of 113 countries included in the food security program. Household-level food security is a key factor in addressing nutritional problems, particularly among populations that are highly vulnerable to nutritional disorders. This study aimed to examine the relationship between food security and protein intake in Selo District, Boyolali. This study employed an observational design with a cross-sectional approach. A total of 108 samples were selected using simple random sampling. Primary data were collected using the Household Food Insecurity Access Scale (HFIAS) questionnaire and a semi-quantitative food frequency questionnaire (SQ-FFQ) through interviewer-administered interviews. Secondary data were obtained from Selo Boyolali Public Health Center records. Data analysis was conducted using correlation analysis. The results showed a significant negative correlation between food security level and protein intake in Selo District, including Tlogolele, Jrakah, and Klakah villages (r = −0.268; p = 0.005). In addition, a significant positive correlation was found between protein intake and nutritional status in the same area (r = 0.191; p = 0.048). In conclusion, there is a significant relationship between food security and protein intake in Selo District, and protein intake also plays an important role in influencing nutritional status.